2016
DOI: 10.1136/bmjopen-2016-012847
|View full text |Cite
|
Sign up to set email alerts
|

Gut feelings in the diagnostic process of Spanish GPs: a focus group study

Abstract: ObjectivesThe gut feelings of doctors can act as triggers and modulators of the diagnostic process. This study explored the existence, significance, determinants and triggers of gut feelings among Spanish general practitioners.DesignQualitative study using focus groups. Thematic content analysis.SettingPrimary healthcare centres in Majorca (Spain).Participants20 purposively sampled general practitioners working in Majorca.ResultsGeneral practitioners were aware of the existence of gut feelings in their diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 28 publications
1
51
0
3
Order By: Relevance
“…35 The Danish cancer pathway for patients with Denmark Cross-sectional 1278 patients Cancer serious non-specific symptoms and signs of cancer -a cross-sectional study of patient characteristics and cancer probability Johansen et al (2012) 39 How does the thought of cancer arise in Norway Qualitative interviews 11 GPs Cancer a general practice consultation? Interviews with GPs Oliva et al (2016) 37 Gut feelings in the diagnostic process of Spain Qualitative focus 20 GPs Cancer Spanish GPs: a focus group study groups RevMan (version 5.3). Finally, qualitative and quantitative data were combined into a descriptive overview of findings.…”
Section: How This Fits Inmentioning
confidence: 99%
“…35 The Danish cancer pathway for patients with Denmark Cross-sectional 1278 patients Cancer serious non-specific symptoms and signs of cancer -a cross-sectional study of patient characteristics and cancer probability Johansen et al (2012) 39 How does the thought of cancer arise in Norway Qualitative interviews 11 GPs Cancer a general practice consultation? Interviews with GPs Oliva et al (2016) 37 Gut feelings in the diagnostic process of Spain Qualitative focus 20 GPs Cancer Spanish GPs: a focus group study groups RevMan (version 5.3). Finally, qualitative and quantitative data were combined into a descriptive overview of findings.…”
Section: How This Fits Inmentioning
confidence: 99%
“…However, child abuse is often more hidden, and the signals are vague. Diagnostic reasoning is generally a mixture of analytical and non-analytical, intuitive aspects, where gut feelings help GPs to navigate safely in uncertain situations [17][18][19]. Previous research among GPs in Europe showed that they acknowledge gut feelings a valuable diagnostic tool [17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…When they do so, they have to ask more specific questions, adopt an even more attentive attitude and observe more accurately to identify the trigger that gave them the sense of alarm. The role of GFs in the GP’s diagnostic process has been studied in countries such as the Netherlands, Belgium, France and Spain 6–9. These studies show two types of GF.…”
Section: Introductionmentioning
confidence: 99%
“…The sense of alarm arises especially when diffuse symptoms are suspected to hide a neoplasm 6 7 9. The role of GFs in the diagnosis of cancer has been little studied so far.…”
Section: Introductionmentioning
confidence: 99%